The rise of shadow banking: Evidence from capital regulation - Rustom Irani; Rajkamal Iyer; Ralf Meisenzahl; José-Luis Peydró (Review of Financial Studies, 2021)
We investigate the connections between bank capital regulation and the prevalence of lightly regulated nonbanks (shadow banks) in the U.S. corporate loan market. For identification, we exploit a supervisory credit register of syndicated loans, loan-time fixed effects, and shocks to capital requirements arising from surprise features of the U.S. implementation of Basel III. We find that less-capitalized banks reduce loan retention, particularly among loans with higher capital requirements and at times when capital is scarce, and nonbanks step in. This reallocation is associated with important adverse effects during the 2008 crisis: loans funded by nonbanks with fragile liabilities are less likely to be rolled over and experience greater price volatility.
Keywords: G01; G21; G23; G28; 330; Financial Crises; Banks; Micro Finance; Non-bank Financial Institutions; Institutional Investors; Government Policy and Regulation